Tips on robotic single-site surgery suture technique - Hye-Sung Moon (Elsevier, 2018)
Objectives: Using the da Vinci single-site platform, surgeons can perform more minimally invasive surgery. However, surgical challenges exist due to the limitations of single-site instrumental movements. To aid in the performance of successful robotic single-site hysterectomy, a new suturing technique using the current set of limited instruments is introduced in this study. Material & methods: New vaginal cuff suturing techniques have been used in 55 robotic single-site hysterectomies in our institute over the past 2 years. A needle driver approach utilizing screwing and advancing the needle driver in the correct direction at an increasing angle from the transverse cuff margin with dragging and formation of an adequate loop of thread was used when suturing the vaginal cuff. Results: Using the new vaginal suturing techniques, easy and firm vaginal cuff closure with reduced operative time relative to previous hysterectomies was achieved. Conclusion: The new vaginal cuff suturing techniques may convince more surgeons to perform robotic single-site hysterectomies more frequently and with greater ease.